Dampak Regulasi Nasional terhadap Kesejahteraan Masyarakat di Kepulauan Maluku - Maria Natalia Syalomita A. Rahanubun; Roberto O.C Seba; Christian H.J de Fretes (Jurnal Hukum Lex Generalis, 2025)
The inequality of development between the mainland and archipelago areas in Indonesia is still a serious problem, especially in the context of policy formulation and implementation which tends to be centralistic and does not take into account local conditions. This research aims to examine the extent to which national regulations can be adapted by the local governments of the archipelago and identify the institutional challenges faced in their implementation. The method used is a qualitative approach with case studies in the archipelago in Maluku Province, including analysis of policy documents, field observations, and in-depth interviews with key actors at the local level. The results of the study show that there is a limitation of the authority of local governments in adapting national regulations to the local context, which has an impact on the low effectiveness of development policies in the archipelago. In addition, weak supervision systems and maladministrative practices have exacerbated inequality in public services and natural resource management. The discussion emphasized the importance of intergovernmental synergy, institutional capacity building, and data-based policy formulation and community participation. Policy reform must start at the local level, by providing more space for the public to be involved in the regulatory formulation process. The conclusions of this study confirm that equitable and sustainable development in the archipelago can only be achieved through an adaptive, participatory, and contextual policy approach.